2013
DOI: 10.1007/s00167-013-2490-3
|View full text |Cite
|
Sign up to set email alerts
|

Thomas Annandale: the first meniscus repair

Abstract: A biographical insight about nineteenth century Scottish surgeon Thomas Annandale (1838-1907), describing his life and his milestone contribution to the orthopaedics field, particularly analysing the first meniscus repair in history, that Annandale performed in 1883 and documented in his original paper titled "An Operation for Displaced Semilunar Cartilage" (1885). The experience of Annandale marks a shift in the treatment of meniscal injuries, by introducing the practice of restoring and repairing the origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
0
24
0
5
Order By: Relevance
“…That is the sense of all historical research, namely, rediscovering the origins [4] to strengthen your own motivation in going onwards looking at the enlightened figures who contributed greatly to shape our profession [5][6][7]. In the present paper we brought into light some glorious moments of the very beginning in the activity of the Société Internationale de Chirurgie Orthopédique et Traumatologiè (SICOT).…”
Section: Resultsmentioning
confidence: 84%
“…That is the sense of all historical research, namely, rediscovering the origins [4] to strengthen your own motivation in going onwards looking at the enlightened figures who contributed greatly to shape our profession [5][6][7]. In the present paper we brought into light some glorious moments of the very beginning in the activity of the Société Internationale de Chirurgie Orthopédique et Traumatologiè (SICOT).…”
Section: Resultsmentioning
confidence: 84%
“…These authors also observed that the numbers of the mice housed in the cage had signifi cant impact on OA severity as group-housed mice demonstrated higher OA score relative to individually housed mice. To establish a more reliable mouse DMM model, Kim et al [ 63 ] suggest that using small cages (75 L × 40 W × 200 H mm 3 ) with limited movement may decrease individual variation and control OA severity; however, animal welfare considerations of limited housing space need to be considered.…”
Section: Mouse Dmm Oa Model and Cage Environmentmentioning
confidence: 99%
“…One hundred and thirty-one years have passed since the first reported operative treatment on the meniscus [14]. Matteo berardo.dimatteo@gmail.com When looking specifically at the history of relevant medical literature, we should first consider "On Fractures", one of the few works inside the so-called Hippocratic Corpus that scholars really consider as a genuine writing by Hippocrates himself (ca 460-370 BC) [19].…”
Section: Introductionmentioning
confidence: 99%